Pediatric Intracavernous Sinus Lesions: A Single Institutional Surgical Case Series and Review of the Literature. Issue 4 (29th March 2019) - Hoshide, Reid; Rennert, Robert C; Calayag, Mark; Gonda, David; Meltzer, Hal; Crawford, John R; Levy, Michael L
Abstract: BACKGROUND: Pediatric intracavernous sinus tumors are exceedingly rare and thus poorly characterized. Their neurosurgical management is challenging and diagnostic, and management guidelines are limited. OBJECTIVE: To report our institutional experience with the surgical resection of pediatric intracavernous sinus tumors. We also compare and contrast our results with the 14 cases of pediatric intracavernous sinus lesions in the current literature. METHODS: A retrospective descriptive analysis of consecutive pediatric patients (ages 0-18 yr) presenting to our institution with a diagnosis of an intracavernous sinus lesion was performed. From January 2012 to January 2017, 5 cases were identified. Eleven patients with secondary invasion of the cavernous sinus (2 meningiomas, 7 pituitary adenomas) or dermoid tumors involving the cavernous sinus (2) were not included in our review. RESULTS: Surgical resection via a frontotemporal orbitozygomatic approach was performed in all cases by a single senior neurosurgeon (M.L.). There were no perioperative or postoperative complications attributable to the surgery or approach. Four of 5 patients remained neurologically stable throughout the perioperative and postoperative period. The fifth patient had a complete resolution of their cranial neuropathies postoperatively. A pathological diagnosis that guided long-term management was obtained in all cases. CONCLUSION: Neurosurgical management of pediatric cavernous sinus lesions can be safely performed and critically guide future therapies. Surgeon familiarity with cavernous sinus and skull-base anatomy is critical to the successful management of these patients. The benefits of surgery should be balanced against the potential complications and need for a tissue diagnosis in children. The senior author had a significant experience with cavernous sinus approaches in adults prior to initiating use of the approach in the pediatric population.